The impact of poor stakeholders involvement in the planning and implementation of construction projects case study: Accra Metropolis, Ghana - Ankukumah, Richard Kwame (2017)
A thesis submitted to the Department of Building Technology, College of Art and Built Environment in partial fulfillment of the requirements for the degree of Master of Science,